Gain-clamped fibre amplifier using an ASE end reflector - Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd; Poopalan, P.; Selvakennedy, S.; Chan, W.Y.; Ahmad, Harith (Elsevier, 2000)
All-optical gain clamping in an erbium-doped fibre amplifier is demonstrated using a broadband fibre Bragg grating that reflects the amplified spontaneous emission centred at 1530 nm with a 14 nm bandwidth. Experiments on an eight-channel wavelength division multiplexing system show promise when the gain is clamped at 21 dB. Gain flatness is less than 0.6 dB across all channels and gain variation is about 0.2 dB over the input signal power range. (C) 2000 Elsevier Science B.V. All rights reserved.